2018
DOI: 10.1007/s11356-018-1311-0
|View full text |Cite
|
Sign up to set email alerts
|

Effects of malathion and nitrate exposure on the zooplankton community in experimental mesocosms

Abstract: Surface waters are likely to be contaminated by both pesticides and fertilizers. Such contamination can result in changes in community composition if there is differential toxicity to individual taxa. We conducted a fully factorial mesocosm experiment that examined the single and interactive effects of environmentally realistic concentrations of nitrate and malathion on zooplankton communities and phytoplankton productivity. Malathion significantly decreased the abundance of total zooplankton, cyclopoid copepo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 39 publications
1
4
0
Order By: Relevance
“…The decrease in cladocerans might have favoured the increase in rotifers, which were more tolerant to CLP, as previously demonstrated for other xenobiotics such as malathion and carbaryl (Hanazato and Yasuno, 1990;Relyea et al, 2005). Consistent with this, field studies found similar effects on species replacement after the application of CLP and other related insecticides (Kaushik et al, 1985;Chang et al, 2005;Smith et al, 2018).…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…The decrease in cladocerans might have favoured the increase in rotifers, which were more tolerant to CLP, as previously demonstrated for other xenobiotics such as malathion and carbaryl (Hanazato and Yasuno, 1990;Relyea et al, 2005). Consistent with this, field studies found similar effects on species replacement after the application of CLP and other related insecticides (Kaushik et al, 1985;Chang et al, 2005;Smith et al, 2018).…”
Section: Discussionsupporting
confidence: 79%
“…2016). The effects of fish predation on zooplankton have been widely studied, as well as the impact of insecticides, with both factors individually having similar direct and indirect effects on community density, composition (species replacement), evenness, size and traits (Relyea and Hoverman, 2006;Laird et al, 2007;Iglesias et al, 2011;Smith et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Oceanographic modifications, induced by global warming, coupled with pollution, are two potential candidates that may explain reduced prey sizes for sardines. Up to 77% of total marine pollution is from terrestrial sources (Williams, 1996) and contaminants such as pesticides, fertilizers, heavy metals and synthetic organic chemicals are all known to affect plankton communities, reducing their diversity and causing irreversible changes in marine ecosystems (Shahidul Islam and Tanaka, 2004;Pérez et al, 2011;Smith et al, 2018). For example, the insecticide Malathion and the herbicide Roundup R significantly decreased copepod abundance, but favored smaller and lower energetic zooplankton (Geyer et al, 2016;Smith et al, 2018).…”
Section: Amplifying Factors and Their Consequencesmentioning
confidence: 99%
“…There is currently a rich and growing body of literature on how pesticides affect individuals and species. Most studies to date have focused on single‐species approaches to assess the organismal responses to pesticide exposure (Delnat et al, 2019; Janssens & Stoks, 2020; Lal et al, 2013; Song et al, 2017; Thoré, Philippe, et al, 2021), or have relied on mesocosm experiments and field surveys to assess how pesticides affect biodiversity and community composition (Andrade et al, 2021; López‐Mancisidor et al, 2008; Mcmahon et al, 2012; Pestana et al, 2009; Smith et al, 2018). Pesticides may not only induce direct lethal (Delnat et al, 2020; Hua et al, 2013; Kafula et al, 2022) but also sublethal effects such as physiological and life history changes (Aliouane et al, 2009; Palma et al, 2009; Thoré, van Hooreweghe, et al, 2021).…”
Section: Introductionmentioning
confidence: 99%